LIVELIHOOD AND LIFE EXPERIENCE OF VICTIMS OF HUMAN TRAFFICKING IN MEXICO - Barragan Codina, Manuel R. (Advances in Social Sciences Research Journal, 2019)
The International Labor Organization estimated that 20.9 million or more individuals worldwide exploited for sex or labor or services through fraud, force or coercion. Nevertheless, the recent Global Slavery Index estimates nearly 46 million people subject to some form of modern slavery in the world today, which represents 0.6 percent of total world population. In the case of Mexico, every year thousands of young women and girls trafficked inside the country for the purpose of sexual exploitation and forced prostitution, often suffer extreme physical, sexual, and psychological exploitation, and it leads to a high risk of unwanted pregnancy and sexually transmitted infections. In this paper we have try to explore the livelihood and daily life experience of trafficked women in Mexico particularly in the case of Monterrey city. Our finding indicates that victims of sex trafficking forced to work all the day and longest period without allowing them to take rest. They also obligate to live in inhumane condition, and in most of the condition, they also do not allow to takes proper food. Moreover, they do not have medical access for any kinds of health problem. The same human is often over looked and pushed into insecure, unsafe and unhealthy working conditions.